Dampak pengalaman karyawan terhadap intensi turnover melalui keterikatan dan kepuasan kerja karyawan - Bella Yunivan Hernanda; Tjahjani Prawitowati; Emma Yulianti (Journal of Business & Banking, 2025)
The study aims to test and analyze the significance of the effect of employee experience on turnover intention, the effect of employee experience on employee engagement, the effect of employee engagement on employee job satisfaction, and the effect of job satisfaction on employee turnover intention as well as the mediating role of job satisfaction and job attachment on the effect of employee experience on turnover intention, This research is descriptive research with a quantitative method approach. This research use an online survey method in the form of a questionnaire to collect data. The data to be collected and used is primary data with a total of 207 respondents. The test tool used in this research is WarpPLS 7.0 software and uses the Partial Lest Square Equation (PLS-SEM) method. The result show a negative and significant effect of employee experience on turnover intention, a positive and significant effect of employee experience on employee engagement, a positive and significant effect of employee engagement on job satisfaction, a positive and significant effect of job satisfaction on turnover intention, and employee engagement and job satisfaction are unable to mediate turnover intention. Companies should ensure that the work environment encourages career paths, good interpersonal relationships, and work-life balance. This is closely related to the final impact, namely turnover intention.